2019
DOI: 10.21608/ajs.2019.43847
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate the Effect of Some Factors Affecting Solubilization of Phosphorus in Rhizosphere

Abstract: The aim of this work was to conduct pot experiment to study the ability of plant roots on solubilizing various sources of phosphorus and factors that may facilitate or inhibit their activity. A split medium split root technique experiment was conducted to study the effect of CaCO3, pH, organic matter (humic acid) and bentonite on the pH, P solubility in the medium and P concentration in bean plants (Vicia faba var. balady). The changes in pH of the lower solution was recorded, also the root exudate was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Also, the same results were found when humic acid was added, but for OSP the P solubility increased more than the double. These results agreed with those obtained by Elhag et al (2019) concerning the effect of humic acid on increasing P availability in washed sand. On the other hand, the effect of these natural organic sources was different when the dissolving bacteria was added, as the values of P solubility increased with compost or humic acid in these sources with more P solubility for OSP than for RP or BS.…”
Section: Incubation Experimentssupporting
confidence: 92%
See 3 more Smart Citations
“…Also, the same results were found when humic acid was added, but for OSP the P solubility increased more than the double. These results agreed with those obtained by Elhag et al (2019) concerning the effect of humic acid on increasing P availability in washed sand. On the other hand, the effect of these natural organic sources was different when the dissolving bacteria was added, as the values of P solubility increased with compost or humic acid in these sources with more P solubility for OSP than for RP or BS.…”
Section: Incubation Experimentssupporting
confidence: 92%
“…This was found in case of without adding or with adding solubilizing bacteria, but the values were generally higher with the later. Elhag et al (2019) reported that, increasing available P in soil by addition of P sources was reflected on increasing P concentration in bean roots and shoots, with high concentrations in shoots more than roots.…”
Section: N P and K Concentrations In Faba Bean Leavesmentioning
confidence: 99%
See 2 more Smart Citations